Smart Mobility dalam Pengembangan Transportasi Berbasis Aplikasi Online Di Indonesia - Novia Sari Ristanti (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
The phenomenon of the Industrial Revolution 4.0 is characterized by the growing development of digital information technology in various fields through business startups, including in the transportation sector. Due to technological advancements and the company's interest in the transportation sector, many regions began to implement the concept of Smart Mobility. Currently in Indonesia there are large companies offering online application-based transportation services, for example Go-jek and Grab. Progress in transportation based on online applications is a competition challenge that requires the representation of digital technology to facilitate people in mobilizing. This research was conducted to find out how the development of online application-based transportation in supporting the application of the concept of Smart Mobility in Indonesia. The development of online transportation in supporting the application of the concept of Intelligent Mobility in Indonesia is done by using the comparative description method, which is comparing indicators of research variables with those carried out in the field. The results of the discussion above, for the discussion prepared later on the response in response to the results of the discussion.